Peranan Internal Audit Terhadap Pengendalian Intern Kas Untuk Menilai Efisiensi Pengelolaan Kas - P, Robert Pius; Magdalena, Annaria; Yesika, Yesika (Institut Bisnis dan Informatika Kesatuan, 2015)
Cash is a current asset of a company that is very attractive and easily diverted by officials and employees for objectives and conditions no in accordance with company's objectives. This may cause a wasting offimds and misuse of cash and therefore cash should be supervised properly, either in its receipts and expenditures. This is ti assure the cash balance in the account actually exists. Therefore, an internal audit department plays a very important role in supporting the internal control to assess the efficiency of cash in the cash management of the company. The purpose of this study is to determine how much the role of intemal audit in PT Shoes Mas to ensure its cash eficient management. The analytical method used is descriptive qualitative, by analyzing the data obtained from the questionnaires and the data provided by the company through observation and interviews. Results of research at PT Sepatu Mas Idaman concluded that the intemal audit PT Shoes Mas Idaman already support the intemal control system in the company, although there are some violations committed, either by employees or oficials ofthe company to the existing intemal control. Keywords: Internal Audit, Internal Control, Cash Management.